Broiler behavior: Influence of thermal stress, age, and period of the day - Sgavioli, Sarah; Santos, Elaine Talita [UNESP]; de Faria Domingues, Carla Heloisa; Castiblanco, Diana Maryuri Correa [UNESP]; Rodrigues, Paulo Henrique Mazza; Zeferino, Cynthia Pieri; Almeida, Ayla Rosa [UNESP]; Boleli, Isabel Cristina [UNESP] (Revista Brasileira de Zootecnia, 2023)
This study evaluated the behavior of broiler chickens subjected to thermal stress during different periods of the day and age of birds. A total of 180 one-day-old male broiler chicks were allocated to three chambers. Each chamber contained five boxes, with 12 chicks/box. Birds were assigned to a completely randomized design. The birds were filmed, and the images recorded every minute during the two periods: morning (from 08:00 to 09:00 h) and afternoon (from 17:00 to 18:00 h), at 7, 14, and 35 d of age. The frequency of the behavioral category (water intake, feed intake, resting, exploration, and comfort) was determined. Data were subjected to variance analysis for mixed models with rearing temperatures (cold, usual, and hot) and age of birds (7, 14, and 35 d) as subdivided plot, and periods of the day (morning and afternoon) as subsubdivided plot. Birds at cold and usual temperatures showed higher feed intake than those at hot temperature in the morning. Birds exposed to cold and usual temperatures explored the environment less frequently at 35 d when compared with 14 d. However, chickens at hot temperature showed decreased exploration according to the increase of age. Birds spent more time feeding during the morning, regardless of age and rearing temperature. Also, during this period of the day, chickens spent most of the time exploring the environment. The frequency of feed intake and exploration decreases with the increase of age. The similarity of behavior between chickens reared at cold and usual temperatures may be due to a change in the thermal comfort zone of the birds. It suggests that the real thermal comfort temperature is between the two temperature ranges studied (cold and usual).
Keywords: animal behavior; birds; heat stress; rearing temperature; welfare